GEOMORPHIC INDEXES APPLIED TO TECTONIC DEFORMATION STUDY: A REVIEW - Santos, Marcilene dos [UNESP]; Bernardes Ladeira, Francisco Sergio; Batezelli, Alessandro (Uniao Geomorfologia Brasileira, 2019)
This work gathers and discusses the major techniques of geomorphic indexes developed by several researchers over time, and currently applied to tectonics/neotectonics/active tectonic deformation study. Drainage is the most sensitive feature to relief changes, especially those related to tectonics and/or climate change, sea level oscillations, or anthropic action. The river sensitivity to relief changes reflects not only their rapid morphological/morphometric and sedimentary response but also the quick adjustment to a near-equilibrium stage in short geological time. It allows inferring recent tectonic activity by identifying regions in erosional disequilibrium in large areas, regardless of geological or geomorphic provinces. Such unique river feature strengthens the significance of identifying anomalous behaviors in studies of tectonic activity, and the evolution of modern environments or paleogeographic reconstitution. Thus, the present review considers the indexes related to quantitative relief features, such as altimetry, hypsometry and slope. And gives special attention to those indexes related to geomorphic and sedimentary responses of rivers to tectonic deformation (deflections, piracy and beheading, avulsion and combing, channel pattern adjustment, longitudinal profile adjustment and SL index, asymmetry factor and basin shape index, sinuosity of rivers and channel pattern, mountain front sinuosity (S-mf), index of active tectonics (I-at), sediment load and flow, etc.). For this purpose, the present study involved a bibliographic review and analysis of such techniques, as well as some cases from more recent works, presenting some indexes applied to the Aiuruoca river (Mantiqueira Hill, State of Minas Gerais) and the Cinzas and Laranjinha rivers, (Cinzas River watershed, State of Parana). The present work aims to support the studying strategy and the process of choosing the existing techniques, as well as to improve understanding and careful application of such current techniques.
Keywords: Geomorphic indexes; Tectonics; Rivers